2019
DOI: 10.9734/jamb/2019/v14i430071
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical and Bacteriological Quality of Drinking Water Sources in Calabar Municipality, Nigeria

Abstract: This study evaluated the physico-chemical and the bacteriological quality of five different sources of drinking water in Calabar metropolis, Nigeria, to give a fair geographical representative of the town and to contribute to our understanding of the quality of drinking water in the metropolis. The physico-chemical characteristics such as pH, temperature, turbidity, conductivity, colour, Iron, dissolved oxygen, Calcium, Magnesium, alkalinity, total hardness, Manganese, Sulphate, Chloride, Phosphate, Sodium, Zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Water is the most essential product that is taken by humans which must be prevented from deterioration in quality. It is also essentials for life and life has evolved in water due to its unique chemical and physical properties 2 . Okorafor et al, 1 highlighted his point of view when they declared that "water functions in a variety of ways within a cell" can't be debated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water is the most essential product that is taken by humans which must be prevented from deterioration in quality. It is also essentials for life and life has evolved in water due to its unique chemical and physical properties 2 . Okorafor et al, 1 highlighted his point of view when they declared that "water functions in a variety of ways within a cell" can't be debated.…”
Section: Introductionmentioning
confidence: 99%
“…Life originated from water, it is the matrix of life and it's also a solvent and medium. Water is also the medium by which diseases such as typhoid fever, dysentery and cholera can be spread from one human to another" 2,3 . Treatment are performed to remove pathogenic micro-organism and also decrease turbidity, eliminate taste, odour, remove nuisance chemicals, such as manganese or iron and soften the water to make it more useful for consumption, laundry and other industrial processes 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Diarrhea remains a major killer in children and it is estimated that 80% of all illness in developing countries is related to water and sanitation; and that 15% of child deaths under the ages of 5 years in developing countries results from diarrheal diseases (Kassie and Hyelom, 2017;Malhotra et al, 2015). The human pathogens that present serious risk of diseases whenever present in drinking water include Salmonella species, Shigella species, Yersinia enterocolitica, Campylobacter species, various viruses such as Hepatitis A virus, Hepatitis E virus, Rotavirus and parasites like Entamoeba histolytica, and Giardia lamblia (Agbo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cassava effluent is a source of pollution, if discharged into the environment before proper treatment [1]. Pollution of our environment occurs when waste water discharged from cassava processing are allowed to spread slowly into the soil or flow into streams or when cassava roots are fermented in surface water like ponds and streams, upstream of drinking water sources [2,3,4,5] reported that suspended solid particles are important pollutants as pathogens are carried on the surface and body of the particles.…”
Section: Introductionmentioning
confidence: 99%
“…A fair volume of the cassava effluent is carried in solution, others have become so finely divided that they exist in a colloidal state, while others go into suspension [3,8]. Water pollution causes nearly 14,000 deaths per day, basically due to contamination of drinking water sources [3,4,8]. The discharge of waste products and contaminants into surface runoff get into rivers through drainage systems, leaching into liquid spills, groundwater and wastewater discharges and littering.…”
Section: Introductionmentioning
confidence: 99%